The influence of leadership style and work environment on the work motivation of employees in the public hosting service, settlement area, and land in Merauke Regency with work discipline as an intervening variable - Ganna, Marthen; Noer, Elly; Chandrawati, Titi (Technium Social Sciences Journal, 2023)
This research was conducted to determine the effect of leadership style and work environment on the work motivation of public housing, residential area, and land affairs officials in Merauke district with work discipline as an intervening variable. The research approach used is quantitative, using the Smart PLS statistical tool. The population in this study were all 120 employees of the Public Housing, Settlement Area, and Land Office of Merauke Regency, but only 105 questionnaires could be analyzed further so that the sample in this study totaled 105 samples. The results of the study show that leadership has a negative and insignificant effect on motivation. Leadership has a negative and insignificant effect on work discipline. Discipline mediates positively and not significantly between leadership variables on work motivation. The work environment has a negative and significant effect on work motivation but a positive and significant effect on work discipline. Discipline mediates a negative and significant relationship between the work environment and significant to work motivation. Meanwhile, discipline has a negative and significant effect on the work motivation of employees of the Public Housing, Settlement Areas and Land Affairs Office of Merauke Regency.